Biogenesis of cellular iron-sulfur proteins: structure, function, and assembly in mitochondria - Lill, Roland (Henry Stewart Talks, 2018)
Structure and functions of iron-sulfur (Fe/S) clusters and proteins, Analysis of Fe/S proteins and their biogenesis, Mechanisms of Fe/S protein assembly in mitochondria, Mitochondrial “Fe/S diseases“